The diagnosis of mitochondrial HMG-CoA synthase deficiency - Zschocke, Johannes; Penzien, Johannes M.; Bielen, Rainer; Casals, Núria; Aledo, Rosa; Pié, Juan; Hoffmann, Georg F.; Hegardt, Fausto G.; Mayatepek, Ertan (The journal of pediatrics, 2002)
Deficiency of 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) synthase, the only disorder exclusively affecting hepatic ketogenesis, is a cause of hypoglycemic coma. We report that the diagnosis can be made by typical laboratory findings (hypoketosis, elevated free fatty acids, normal acylcarnitines, specific urinary organic acids) during acute episodes. (J Pediatr 2002;140:778-80)